Optical selection of quasars: SDSS and LSST. Issue Volume 9:Issue S304(2013) (25th July 2014) - Ivezić, Željko; Brandt, W. Niel; Fan, Xiaohui; MacLeod, Chelsea L.; Richards, Gordon T.; Yoachim, Peter
Abstract: Over the last decade, quasar sample sizes have increased from several thousand to several hundred thousand, thanks mostly to SDSS imaging and spectroscopic surveys. LSST, the next-generation optical imaging survey, will provide hundreds of detections per object for a sample of more than ten million quasars with redshifts of up to about seven. We briefly review optical quasar selection techniques, with emphasis on methods based on colors, variability properties and astrometric behavior.